Care-educational technologies to home care of children that tracheostomy: integrative review (Research, Society and Development, 2022)
Background: care-educational technologies are the union of education and care and are charactized by the development of new ways of teaching, searching for relationship building among those involved, with the aim to promote empowerment, bond, autonomy and well-being of patients, relatives and profissionals. Objective: to identify the care-educational technologies that can help with training of relatives and caretakers to make the tracheostomy tube´s care of children at home. Methods: It is treated of an integrative literature review made like peer review the databases of Scopus, the Virtual Health Library, Publisher Medline and at theses and dissertations´s catalogue of Coordination for the Improvement of Higher Education Personnel in March 2021, limiting to studies published in the last ten years, following the recommendations of Method of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: it has been identified 1535 studies, to which it was applied the inclusion and exclusion the remaining 495 studies; therefore, from the reading of titles and/or abstracts, 31 articles were selected from which of the seven articles constituted the final sample: one national and six international. Six care-educational technologies have been identified: simulation, demonstration, printed materials, audiovisual materials, protocols and round of conversation. Most studies described the concomitant use of two or more technologies to aid in care. Conclusions: the care-educational technologies proved to be innovative, complete and objective, highlighting the nurse´s active participation on actions of health education.